Recent Advances in the Role of Discoidin Domain Receptor Tyrosine Kinase 1 and Discoidin Domain Receptor Tyrosine Kinase 2 in Breast and Ovarian Cancer - Chen, Li; Kong, Xiangyi; Fang, Yi; Paunikar, Shishir; Wang, Xiangyu; Brown, James A. L.; Bourke, Emer; Li, Xingrui; Wang, Jing (Frontiers in Cell and Developmental Biology, 2021)
Abstract: Discoidin Domain Receptor tyrosine kinases (DDRs) are a class of Receptor Tyrosine Kinase’s (RTKs), and their dysregulation is associated with multiple diseases (including cancer, chronic inflammatory conditions and fibrosis). The DDRs family (DDR1a-e and DDR2) are widely expressed, with predominant expression of DDR1 in epithelial cells and DDR2 in mesenchymal cells. Structurally, DDRs consist of three regions (an extracellular ligand binding domain, a transmembrane domain, and an intracellular region containing a kinase domain), with their kinase activity induced by receptor-specific ligands binding. Collagen binding to DDRs stimulates DDR phosphorylation activating kinase activity, signaling to MAPK, integrin, TGF-β, insulin receptor, and Notch signaling pathways. Abnormal DDR expression is found in a range of solid tumors (including breast, ovarian, cervical liver, gastric, colorectal, lung and brain). In tumorigenesis abnormal activation of DDRs can lead to invasion and metastasis, via dysregulation of cell adhesion, migration, proliferation, secretion of cytokines and extracellular matrix remodeling. Differential expression or mutation of DDR1 or DDR2 correlate with pathological classification, clinical characteristics, treatment response and prognosis. Here, we discuss the discovery, structural characteristics, organizational distribution and DDR-dependent signaling. Importantly, we highlight the role of DDRs in the development and progression of breast and ovarian cancer.